Adaptasi dan Mitigasi Bencana Tanah Longsor Melalui Penguatan Kapasitas Masyarakat dan Peningkatan Produktivitas Lahan Melalui Sistem Agroforestri - Nugroho, Prasetyo; Soedjoko, Sri Astuti; Kusumandari, Ambar; Marhaento, Hero (2013)
Pogalan village, Sub-district Pakis, Magelang, is located in upper part of Mount Merbabu. It consists of 13 hamlets which is located in the area of undulating to very steep slopes (60.30%) with 18.97% of its area has high to very high potential landslide hazard. The objectives of this study were improved the knowledge, understanding and public awareness of environmental issues, establishment of community based disaster response groups (KMTB) and applications of agroforestry system as mitigation and adaptation efforts to prevent landslides hazard.This study was carried out by using several approaches, identification of potential and problems by using interview and focus group discussion; education and community empowerment through the provision of materials and field trips; establishment of community based disaster response groups; introduction of agroforestry system as a form of adaptation and mitigation of landslides hazard. Results showed that the capacity building through enhancement of knowledge and understanding of landslide-prone areas was an important component in terms of adaptation and mitigation of landslide hazard area. It was able to mobilize and encourage the community to increase their efforts in order to improve their environmental conditions by planting trees such as cemara gunung (± 900 seeds) and suren (± 3000 seeds) in agricultural land and landslide-prone area through agroforestry system. In the other hand, establishment of community based disaster response group in Pogalan indicates the seriousness of community to adapt and mitigate land slide hazard independently.